(untitled) (Quinto Sol, 2022)
This article historicizes the educational system in northern Patagonia, starting from a periodization that encompasses the 19th century from the first schools of first letters and charitable societies, to analyze the transition from communal and religious schools to Law 1420 schools. For this reason, we go through the creation of educational institutions, territories and functions that were configured between the mid-19th century and the beginning of the 20th century. We incorporate sources from school inspections, reports from governors of National Territories and the National Education Council. The building of a modern educational system in northern Patagonia was the product of the links between the national State, local governments and the actions of the Church, initially from the Lazarist congregation and after the military conquest, the arrival of Salesian congregations, Salesians and Daughters of Mary Help of Christians.